A Systematic Review On Green Banking Disclosure - Windasari Rachmawati (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This paper presents a systematic review of the topic of Green Banking Disclosure (GBD). GBD has been a growing concept since 2008, with its development bringing about changes, both in terms of the natural and social environments. As such, it is crucial to give it due attention. The study reviewed 50 papers, including 65 empirical ones, and yielded four main findings. Firstly, in terms of theory, legitimacy theory, stakeholder theory, and the concept of Spider profit growth, which serves as an indicator of a company's fund utilization efficiency, were prevalent in the literature. These theories provide a basis for evaluating company management performance, motivating management, and controlling economic resource allocation, ultimately aiding in forecasting future profits and economic events. Secondly, the Green Coin Rating (GCR) concept, comprising six points, played a significant role in the discourse on green banking. Thirdly, the majority of GBD studies were conducted in Muslim-majority countries. The research population included all financial reports of Islamic Commercial Banks during the period 2016-2019. The sample consisted of nine Islamic Commercial Banks that published annual reports up to 2019 and met the criteria for implementing the Green Banking concept. The study suggests that future research endeavors should consider integrating both primary and secondary data to assess the implementation of Green Banking and green financing in banking institutions. This approach would lead to a more comprehensive understanding of the subject and provide a more communicative perspective for customers.